2002
DOI: 10.1038/nature01326
|View full text |Cite
|
Sign up to set email alerts
|

The immunopathogenesis of sepsis

Abstract: Sepsis is a condition that results from a harmful or damaging host response to infection. Many of the components of the innate immune response that are normally concerned with host defences against infection can, under some circumstances, cause cell and tissue damage and hence multiple organ failure, the clinical hallmark of sepsis. Because of the high mortality of sepsis in the face of standard treatment, many efforts have been made to improve understanding of the dysregulation of the host response in sepsis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
1,984
3
97

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,355 publications
(2,149 citation statements)
references
References 74 publications
26
1,984
3
97
Order By: Relevance
“…The earliest and most potent proinflammatory cytokine released by the host in response to infection, has an essential role in the development of infectious disease [15,16,39,40]. Here we show that proinflammatory cytokines can be constitutively produced in mammary glands of healthy sows at parturition.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The earliest and most potent proinflammatory cytokine released by the host in response to infection, has an essential role in the development of infectious disease [15,16,39,40]. Here we show that proinflammatory cytokines can be constitutively produced in mammary glands of healthy sows at parturition.…”
Section: Discussionmentioning
confidence: 62%
“…the production of these proinflammatory cytokines in inoculated mammary glands did not differ between the two groups. Possible explanation for this discrepancy between systemic and local proinflammatory cytokine levels might be that proinflammatory cytokines could also be produced elsewhere but the site of bacterial inoculation [1,8,12,15]. Alternatively, there might be a larger diffusion of cytokines into the blood in the sows with clinical signs of mastitis attributable to the inflammatory damage of mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Studies confirmed that single nucleotide polymorphisms (SNPs) in some particular genes, such as tumor necrosis factor locus, interleukin-1 receptor antagonist, plasminogen activator inhibitor-1 and so on, play a critical role in sepsis. 3,4 Defensins are cysteine-rich cationic antimicrobial polypeptides with three disulfide bridges and are expressed in plants, insects and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In Gram-positive bacteria, peptidoglycan and lipoteichoic acid in the cell wall are possible sepsis-inducing molecules [4]. Staphylococcus aureus, a Gram-positive bacterium, often causes toxic shock syndrome by producing toxic shock syndrome toxin-1 (TSST-1) [5] or by inducing proinflammatory cytokines, such as TNF-a, IL-1b, and IL-6 in infected animals. Therefore, S. aureus is considered an appropriate Gram-positive bacterium for the study of sepsis [6].…”
Section: Introductionmentioning
confidence: 99%